Crystallization behaviour of new poly(tetramethyleneterephthalamide) nanocomposites containing SiO2 fillers with distinct morphologies - Esteves, Ana Catarina C. (2005)
Polyamide-based nanocomposites containing surface-modified SiO2 nanofillers with different morphologies were prepared by in situ polymerisation. The nanocomposites microstructure was investigated by scanning electron microscopy, which showed a high degree of dispersion of the fillers. The isothermal crystallization kinetics, recorded with a differential scanning calorimeter, has shown a strong influence of the nanofillers morphology on the poly(tetramethyleneterephthalamide) crystallization behaviour. The strong nucleating effect of the inorganic substrate is interpreted as the combined result of a lower activation energy for the primary nucleation and a higher activation energy for the transport of chain stems to the growing lamellae.